EEG recordings as biomarkers of pain perception: where do we stand and where to go? - Zis, Panagiotis; Liampas, Andreas; Artemiadis, Artemios; Tsalamandris, Gabriela; Neophytou, Panagiota; Unwin, Zoe; Kimiskidis, Vasilios K.; Hadjigeorgiou, Georgios M.; Varrassi, Giustino; Zhao, Yifan; Sarrigiannis, Ptolemaios Georgios (Springer, 2022)
Introduction: The universality and complexity of pain, which is highly prevalent, yield its significance to both patients and researchers. Developing a non-invasive tool that can objectively measure pain is of the utmost importance for clinical and research purposes. Traditionally electroencephalography (EEG) has been mostly used in epilepsy; however, over the recent years EEG has become an important non-invasive clinical tool that has helped increase our understanding of brain network complexities and for the identification of areas of dysfunction. This review aimed to investigate the role of EEG recordings as potential biomarkers of pain perception. Methods: A systematic search of the PubMed database led to the identification of 938 papers, of which 919 were excluded as a result of not meeting the eligibility criteria, and one article was identified through screening of the reference lists of the 19 eligible studies. Ultimately, 20 papers were included in this systematic review. Results: Changes of the cortical activation have potential, though the described changes are not always consistent. The most consistent finding is the increase in the delta and gamma power activity. Only a limited number of studies have looked into brain networks encoding pain perception. Conclusion: Although no robust EEG biomarkers of pain perception have been identified yet, EEG has potential and future research should be attempted. Designing strong research protocols, controlling for potential risk of biases, as well as investigating brain networks rather than isolated cortical changes will be crucial in this attempt.
Keywords: EEG; Electroencephalogram; Pain; Perception; Biomarker